2015
DOI: 10.7454/mst.v18i3.431
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Application of a Compact Compound-Eye Camera

Abstract: A multi-functional compound-eye endoscope enabling multi-spectral imaging and variable field-of-view is presented, which is based on a compact compound-eye camera called TOMBO (thin observation module by bound optics). Narrow-band filters attached to some lenses provide snap-shot multi-band images. Fixed and movable mirrors are introduced to control the field of view, which realizes several observation modes such as three-dimensional shape measurement, wide field-of-view, and close-up observation. AbstrakPengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Beam splitters were used since the 1950s in television cameras [24], which divide light beams into different fractions similar to prisms. Interferometer based techniques [36], filtered lenslet arrays [37], division of focal plane polarimeters [38], spectrometers [39], multi-view multi-spectral mirror systems [40], and tunable sensors [41] can be named, too. These methods are tied to specify problems and are used in few industrial and professional applications.…”
Section: Related Multi-spectral Imaging Techniquesmentioning
confidence: 99%
“…Beam splitters were used since the 1950s in television cameras [24], which divide light beams into different fractions similar to prisms. Interferometer based techniques [36], filtered lenslet arrays [37], division of focal plane polarimeters [38], spectrometers [39], multi-view multi-spectral mirror systems [40], and tunable sensors [41] can be named, too. These methods are tied to specify problems and are used in few industrial and professional applications.…”
Section: Related Multi-spectral Imaging Techniquesmentioning
confidence: 99%
“…Optical beam scanning methods are also promising to increase the FoV of the endoscopic imaging systems [ 16 , 17 ]. Kagawa et al showed the possibility to increase the FoV of endoscopes by using a compact compound-eye camera [ 18 ]. Although these approaches offer advantages in terms of image resolution and aberrations, complicated optical and electronic-mechanical designs of the components lessen their durability and stability.…”
Section: Introductionmentioning
confidence: 99%